The effect of root hairs on root water uptake is determined by root–soil contact and root hair shrinkage - Duddek, Patrick; Ahmed, Mutez Ali; Javaux, Mathieu; Vanderborght, Jan; Lovric, Goran; King, Andrew; Carminati, Andrea (The New phytologist, 2023)
Summary The effect of root hairs on water uptake remains controversial. In particular, the key root hair and soil parameters that determine their importance have been elusive. We grew maize plants (Zea mays) in microcosms and scanned them using synchrotron‐based X‐ray computed microtomography. By means of image‐based modelling, we investigated the parameters determining the effectiveness of root hairs in root water uptake. We explicitly accounted for rhizosphere features (e.g. root–soil contact and pore structure) and took root hair shrinkage of dehydrated root hairs into consideration. Our model suggests that > 85% of the variance in root water uptake is explained by the hair‐induced increase in root–soil contact. In dry soil conditions, root hair shrinkage reduces the impact of hairs substantially. We conclude that the effectiveness of root hairs on root water uptake is determined by the hair‐induced increase in root–soil contact and root hair shrinkage. Although the latter clearly reduces the effect of hairs on water uptake, our model still indicated facilitation of water uptake by root hairs at soil matric potentials from −1 to −0.1 MPa. Our findings provide new avenues towards a mechanistic understanding of the role of root hairs on water uptake. See also the Commentary on this article by Boursiac & Bauget 240: 2173–2175.